Penggunaan Sistem Aplikasi Pada Sekolah MAN 2 Model Medan - Ade Irvan Margolang; Jogi Pras; Khairul Amri Silalahi; M Rezi Syahbanda Nst; Maulidayani M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Use of computer application systems in school management or learning for students at the Man 2 Model Medan school which is located on Jl. Willem Iskandar No. 7A, Medan, North Sumatra 20222, aims to find out what applications are used by the Man 2 Model Medan school. The application systems used are Microsoft Word, Microsoft Excel, Google Classroom, and Google Form. The Google Classroom application was only used during the pandemic caused by the Covid-19 virus, but the other three applications are still used today by the Man 2 Model Medan school.